2013
DOI: 10.1159/000356255
|View full text |Cite
|
Sign up to set email alerts
|

Can the R.E.N.A.L Nephrometry Score Preoperatively Predict Postoperative Clinical Outcomes in Patients Undergoing Open and Laparoscopic Partial Nephrectomy?

Abstract: Aim: We evaluate whether the preoperative R.E.N.A.L Nephrometry Score (RNS) can predict the postoperative outcomes in patients undergoing either an open or laparoscopic partial nephrectomy. Patients and Methods: We retrospectively calculated the RNS of 128 patients who underwent either an open partial nephrectomy (OPN) (n = 38) or laparoscopic partial nephrectomy (LPN) (n = 90) between 2003 and 2011. Patients were categorized into low, moderate or high complexity groups based on RNSs. Intra-operative warm isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
(41 reference statements)
3
14
0
Order By: Relevance
“…Nephrometry scoring systems, such as the C‐index (centrality‐index), PADUA (Preoperative Aspects and Dimensions Used for an Anatomical score) and R.E.N.A.L. score (consists of [R]adius [tumour size as maximal diameter], [E]xophytic/endophytic properties of the tumour, [N]earness of tumour deepest portion to the collecting system or sinus, [A]nterior [a]/posterior [p] descriptor and the [L]ocation relative to the polar line), may assist in decision‐making and planning for PN .…”
Section: Discussionmentioning
confidence: 99%
“…Nephrometry scoring systems, such as the C‐index (centrality‐index), PADUA (Preoperative Aspects and Dimensions Used for an Anatomical score) and R.E.N.A.L. score (consists of [R]adius [tumour size as maximal diameter], [E]xophytic/endophytic properties of the tumour, [N]earness of tumour deepest portion to the collecting system or sinus, [A]nterior [a]/posterior [p] descriptor and the [L]ocation relative to the polar line), may assist in decision‐making and planning for PN .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed comparable PSM rates for central and peripheral tumors [51], others a higher risk for central located tumors [52,53]. In the last years, some studies stratified PSM rates according to the risk categories defined by nephrometry scores [8,16,34]. No study demonstrated a significant impact of nephrometry score on risk of PSMs.…”
Section: Discussionmentioning
confidence: 99%
“…A full‐text review of the last 127 articles excluded those articles that could not obtain data and did not conform to the type of research. A total of 20 studies met the requirements of meta‐analysis …”
Section: Resultsmentioning
confidence: 99%